Effects on banaba extract on the carbohydrate metabolism in fasted normal (non diabetic) and diabetic rats. - Yap, Nida
Ten percent banaba extract at a dose of 0.6 ml/100 g body weight was observed to lower the plasma glucose levels in fasted rats. Intraperitoneal glucose tolerance test showed a higher plasma glucose level in banaba treated rats as compared to that of the distilled water treated rats 30 minutes after the administration of banaba. This could be due to the presence of glucagon-stimulating substances like amino acids and glucose in the plant extract. However, the plasma glucose levels in banaba treated rats were observed to normalize at a faster rate than those of the distilled water treated rats. Hepatic glycogen content on the 3rd hour of intraperitoneal glucose tolerance test was higher in the banaba treated rats. On the 3rd hour of the intraperitoneal glucose tolerance test, glucagon activity could have been controlled by the hypoglycemis principles in banaba thereby resulting to the faster elimination of blood glucose concentration and net glycogenesis in the hepatic tissues. Correlation studies revealed that the fasting plasma glucose concentration in normal (non-diabetic) and diabetic rats at zero-time and one hour after banaba administration is significantly and positively related to the hepatic glycogen content of the same rats. It is therefore, possible that hepatic glycogenesis induced by banaba was also increased with higher blood glucose concentration. Determination of glycosylated hemoglobin values in diabetic rats treated daily with banaba was done to see whether the hypoglycemic property of banaba may be reflected in lowered percentages of glycosylated hemoglobin. Since the mean red cell life span in rats has been reported to be considerably shorter than the life span of human RBC, the determination of glycosylated hemoglobin in RBC of rats may not be as sensitive a parameter for measuring ?average? glucose levels as it could be for man.